PENGARUH EDUKASI GIZI PADA ORANG TUA DALAM UPAYA PENCEGAHAN STUNTING: SYSTEMATIC REVIEW - Kana Wadu, Novita Marcelina; Mediani , Henny Suzana; Nurhidayah, Ikeu (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2024)
Stunting is a health problem experienced by toddlers in the world today. The World Health Organization (WHO) states that Indonesia is the third country with the highest prevalence of stunting under five in Southeast Asia (29.6%). Stunting is one of the problems of malnutrition that may have a negative impact on child development. Stunting prevention efforts can be carried out through specific nutrition interventions and sensitive nutrition interventions. This effort can be done through nutrition education which is a part of health education and promotion activities, which are health planning efforts to change individual behavior in the health sector. The purpose of this systematic review is to comprehensively examine the effect of nutrition education on stunting prevention and the effective methods that can be used for educational programs. A comprehensive search strategy is carried out using 4 key databases, namely, Pubmed, ProQuest, EBSCO host and Science Direct from 2012-2021 as well as through the Google Scholar Search Engine. The articles used are primary resources using keywords, namely parents, nutrition education and health promotion, prevention of stunting in children, randomized trials and quasi-experiments. Data analysis was carried out with a narrative approach. Based on the search results, found 425 articles but only 9 articles that meet the criteria. The articles obtained prove that nutrition education has an effect on the nutritional status of children which can also be an effort to prevent stunting. Methods that can be used in conducting nutrition education are home visits, counseling, teaching, demonstrations, and discussions. Through these methods nurses can assist in maximizing the implementation of nursing care for stunting prevention through education as a preventive promotive effort.